DIFFERENTIAL DIAGNOSIS OF HEREDITARY SYNDROME OF HYPOCHOLESTEROLEMIA BY USING EXOMIC SEQUENCING - A. I. Yershova; N. V. Shcherbakova; A. A. Suvorova; E. Y. Hlebus; I. V. Sidonets; A. N. Meshkov; S. A. Boytsov (Рациональная фармакотерапия в кардиологии)
Clinical case study is described. Patient D, 55 years old, applied to the Lipid clinic of State Research Centre for Preventive Medicine because of low blood cholesterol level. Results of the differential diagnosis of the hypocholesterolemia syndrome by using exomic sequencing are presented. This method allows to sequence the majority of regions of genome containing exons, protein-coding parts of genes. Heterozygous mutation in the gene for APOB (5 nucleotides deletion) was found out in the patient by using exomic sequencing. This mutation leads to a premature stop codon with violation of apolipoprotein B-100 synthesis and causes inherited monogenic disease - family hypobetalipoproteinemia.